Analisis kualitas layanan TI SIPATU UMRI menggunakan service operation ITIL V.3 - Edo Arribe; Putri, Nurhidayah (Universitas Muhammadiyah Riau, 2023)
This study analyzes the quality of Information Technology (IT) services using the ITIL V.3 Service Operation framework in the Integrated Academic Service System (SIPATU) at the University of Muhammadiyah Riau. SIPATU is used as an administrative system and employee correspondence service at universities. However, the use of this website is not optimal due to the lack of assistance in operation and the lack of notification via email. ITIL V.3 is a framework for designing, developing, operating and improving IT services in enterprises. The research aims to evaluate the quality of IT services at SIPATU, ensuring IT supports business processes and resources with proper responsibility and risk management. The research objective is to provide a clear picture of the quality of IT services at SIPATU and to propose ideas for improving IT services in the tertiary environment. Through this analysis, it is expected to be able to identify the potential for improving the quality of IT services at SIPATU and formulate appropriate strategies. The conclusion of this research will provide guidance for universities and similar institutions in optimizing the use of IT services to support administrative efficiency and better services.